4(-x+3)=-2(2x-6)

Simple and best practice solution for 4(-x+3)=-2(2x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-x+3)=-2(2x-6) equation:


Simplifying
4(-1x + 3) = -2(2x + -6)

Reorder the terms:
4(3 + -1x) = -2(2x + -6)
(3 * 4 + -1x * 4) = -2(2x + -6)
(12 + -4x) = -2(2x + -6)

Reorder the terms:
12 + -4x = -2(-6 + 2x)
12 + -4x = (-6 * -2 + 2x * -2)
12 + -4x = (12 + -4x)

Add '-12' to each side of the equation.
12 + -12 + -4x = 12 + -12 + -4x

Combine like terms: 12 + -12 = 0
0 + -4x = 12 + -12 + -4x
-4x = 12 + -12 + -4x

Combine like terms: 12 + -12 = 0
-4x = 0 + -4x
-4x = -4x

Add '4x' to each side of the equation.
-4x + 4x = -4x + 4x

Combine like terms: -4x + 4x = 0
0 = -4x + 4x

Combine like terms: -4x + 4x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 11=5(x-4)-(x-7) | | X=4(x+3)-6 | | b-1+7b=28 | | k/10=100 | | 0.1(x+60)-0.04(x-50)=5 | | 6(6x+7)=6 | | 24-2y=8y-7 | | -6a+24= | | 5+3=-4x+47 | | 6=6/10 | | 7y+12=3y-4 | | -4/3u-6=7/3u+8 | | -(4x-4)-(3x-5)+4=-9(x-1)-(2x+7)+3 | | -x-18= | | x+5-11=-3 | | (2v+9)(8-v)=0 | | 4x^3y+12x^2y-8xy= | | -(4x-4)-(3x-5)+5=-9(x-1)-(2x+7)+3 | | 6v+10=9v+9 | | 1+2x-x^2=0 | | 0.1(3.2+2x)+1/2(3-x/5)=0 | | 8x^3+18x^2-10x= | | X/31=17 | | -1.5-6x=26.7 | | 9/6=11/8 | | 3x+12-4= | | -1/3x=-5/6 | | 3(5x-2)=19 | | M-4-3m=-2m-3-1 | | (13x-6)-6(2x+2)=-6 | | 400+300/20 | | 0.5x+6=x+5/3 |

Equations solver categories